SUJET : LA RESISTANCE AU CHANGEMENT CHEZ DES FEMMES VIOLENTES EN COTE Dâ€™IVOIRE: CAS DES EXCISEUSES - Koudou, Opadou; Fatoumata, Traore; Bakayoko, Ismaila (European Scientific Journal, ESJ, 2015)
The state of CÃ´te dâ€™Ivoire, has since 1998 undertaken a fight against Female Genital Mutilation (FGM), through actions of prevention, enforcement and management of circumcisers. In 2014, according to UNICEF more than 38% of circumcised women and the practice remains value by more than 14% of the population. This study aims to identify the factors of resistance to change among women circumcisers. The site is Mankono (town in the center west of CÃ´te d’Ivoire), 80 people participated in the survey. Three interacting variables explain resistance to change: The commitment to socio-cultural values linked to the promotion of female circumcision; income or socio-economic gain and low social control. An education policy centered on the girl could mitigate in short-term this phenomenon.